A informação no projeto de coleta seletiva de papel nas unidades pertencentes `a UFMG - Daniela Assis Alves Ferreira (2003)
It analyzes the process of information transfer accomplished by the Solid Residues Studies Group - GERESOL, in the settlement of Paper Selective Collecting Project at UFMG. It also investigates the public's sensitization about selective collecting and environmental education, under the eyes of those responsible for its setting. Among the eleven units where the Paper Selective Collecting Project was settled, six units were chosen: Pedagogic Center, Pharmacy School, Nursing School, Engineering School, Geography Science Institute and General Services Department. The theory chosen was about the information and society, information transfer, environmental information and social marketing, solid residues, selective collecting and recycling, at Belo Horizonte and UFMG. The chosen methodological approach was the descriptive research. The GERESOL Coordinator and the responsible for the settlement of the Project in the chosen units have formed the universe and the sample worked in this case study. The instruments used for the data collection were the documental analysis and the semi-structured interview. Its concluded that the Paper Selective Collecting Project at UFMG was quite below what was expected, even having taken place the process of information transfer. A larger institutional demand in relation to the commitment along with people's participation and, mainly, a reflection on the paper of each one in relation to the environment, could probably assure the success of a Project as that.